Exploring Consumer Behavior on Product Longevity as a Pathway to Product-Service System Adaptation - Brask, Lauritz Gjedsted; Greve, Niels-Peter; Hansen, Andreas Kornmaaler (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The growing environmental challenge of consumer electronic waste has become increasingly urgent and is projected to reach 82 million tons by 2030. This paper examines product-service systems (PSS) as a potential approach to minimize e-waste and extend overall product longevity and circularity. The relationships with electronic devices and perceptions of product longevity and ownership versus leasing were explored among 20 participants aged 21 to 65, all from Denmark. Insights gained provided a basis for identifying key technological (e.g., software obsolescence) and psychological (e.g., endowment effect, mistrust of leasing) barriers to PSS adoption. A six-step user-centric PSS model is proposed, advocating product-oriented services where consumers maintain ownership but receive company maintenance and repair. The Ownership PSS model underlines consumer trust via transparent pricing, flexible solutions, and alignment with EU right-to-repair policies. This research highlights the need for further quantitative assessment (e.g., life cycle analysis) and broader cultural sampling to strengthen adoption pathways in the electronics sector.